Blastocystis: Pathogen or Passenger? An Evaluation of 101 Years of Research - Mehlhorn, Heinz; Tan, Kevin S. W.; Yoshikawa, Hisao (Parasitology Research Monographs, 2012)
The stages of Blastocystis have been known for 101 years. However, many facts are still disputed, e.g. even the question whether it is a true pathogen or a commensal present in sometimes life-threatening diarrheas. The present book evaluates in chapters contributed by renowned researchers the latest findings on: •Landmarks in the discovery of Blastocystis •Epidemiology, transmission and zoonotic potential •Morphology of human and animal Blastocystis isolates •Clinical aspects of Blastocystis infections •Behavioral decision analysis: what makes us sick? •Blastocystis-host interactions •Molecular approaches on the systematical position •Genetic polymorphism •Blastocystis from a statistical point of view •Diarrheas due to different agents of disease •Zoonotic diseases in comparison As such, this book provides a broad range of information for people working in this field, for physicians and veterinarians who are confronted with clinical cases, teachers, students and technical staff members in the fields of microbiology, parasitology and diagnostic methods.